Implementasi Sistem Penyusutan Arsip Inaktif Di Unit Tata Usaha SMK Ma’Arif NU Doro Kabupaten Pekalongan - Aria Mulyapradana (Widya Cipta - Jurnal Sekretari dan Manajemen, 2018)
Abstract  This study aims to determine the depreciation of inactive archives at SMK Ma'arif NU Doro Pekalongan Regency. Measurements using inactive archives management include the determination of archive retention schedules, filing assessments, filing depreciation systems, archive transfer, archiving destruction, archive submissions and archives. The main question in this study is how the system of inactive archive depreciation in the Unit Administration SMK Ma'arif NU Doro Pekalongan Regency? The results of this study showed that the inactive filing depreciation procedure conducted by SMK Ma'arif NU Doro Pekalongan District is quite good. This will support effective archiving governance or work procedures by standardizing guidelines on the governance or work of the archives and enhancing the skills or skills of employees handling the archives. Keywords: Depreciation, Archives, Inactive Archives